South China Sea cooperation : we should not wait for another disaster - Hasjim Djalal (2014)
Cooperation between the littoral states in the search for Malaysia Airlines flight 370 in the South China Sea has prompted calls for more joint activities amongst them. The South China Sea Workshop Process started in 1989 identified many such opportunities. It may be time to revisit them.